China's "U-Shaped Line" Claim in the South China Sea: Any Validity Under International Law? - Miyoshi, Masahiro (Ocean Development & International Law, 2012)
China's recent claims to a large "U-shaped" area in the South China Sea, involving the disputed Spratly and Paracel Islands, has given rise to a number of serious criticisms not only from neighboring states, but also some states beyond the region. The claim also raises a number of theoretical questions, including whether historic title claims without hard evidence have validity under international law. This article explores this and other issues raised by China's U-shaped claim.